Fatal Scedosporiosis in Multiple Solid Organ Allografts Transmitted From a Nearly‐Drowned Donor. Issue 3 (29th January 2015) - Kim, S.‐H.; Ha, Y. E.; Youn, J.‐C.; Park, J. S.; Sung, H.; Kim, M.‐N.; Choi, H. J.; Lee, Y.‐J.; Kang, S.‐M.; Ahn, J. Y.; Choi, J. Y.; Kim, Y.‐J.; et al.
<x xml:space="preserve">Abstract</x> Scedosporium spp. is the most common mold infection in pneumonia resulting from near‐drowning. Three fatal scedosporiosis cases developed after solid organ transplantation, probably transmitted from the nearly‐drowned donor. One heart transplant recipient and two kidney transplant recipients developed fatal scedosporiosis following deceased donor transplantation from the same donor, a nearly‐drowned victim of a suicide attempt. Genotypically, indistinguishable strains of Scedosporium auratiacum were recovered from the three recipients. Two liver transplant recipients from the same donor received prophylactic voriconazole without any subsequent signs of infection. To determine the safety of donation from nearly‐drowned donors, a national traceback investigation was also performed of the causes of deaths in all transplant recipients who received organs from drowned donors between 2001 and 2013. Over 13 years, 2600 deceased donor transplants were performed in Korea. Among these 2600 deceased donor transplants, 27 (1%) victims of drowning donated their organs. From these 27 donors, 84 patients received organ transplants and 18 died, including the above three. We found no microbiologic evidence of invasive mold transmission from the nearly‐drowned donors to the other 15 recipients. Although disseminated infection in the donor could not be demonstrated by culture, undiagnosed disseminated donor infection and transmission of Scedosporium spp. should be considered in near‐drowning events.